Chronic consequences of atrazine exposure on growth, proximate composition and histological integrity in Clarias gariepinus and its hybrid progeny - K.P. Okpala-Ezennia; A.A. Nlewadim; C.F. Ikeogu; T.C. Okoye (Environmental Pollution and Management)
This study examined the chronic effects of atrazine exposure on Clarias gariepinus and its hybrid (Heterobranchus longifilis ♀ × Clarias gariepinus ♂) over 90 days, following an acute toxicity bioassay. The study aimed to assess dose-dependent impacts on growth, behavior, proximate composition, and histopathology. Sublethal concentrations of atrazine (0, 0.6, 1.3, and 2.5 mg/L) were used to simulate environmentally relevant exposure levels. Behavioral changes such as reduced activity, loss of balance, and decreased appetite, were observed at higher concentrations. Growth analysis revealed significant differences (P < 0.05), with the highest growth rate of 95.90 ± 0.40 g in the hybrid control group and the lowest growth rate of 16.47 ± 0.60 g at the highest concentration in the hybrid group. Proximate composition showed a significant reduction in protein and lipid content in exposed groups compared to controls (P < 0.05). Histopathological examination revealed severe tissue damage in hybrids, which includes liver congestion, inflammation, and hepatocellular steatosis, along with gill arterial disintegration and hypertrophy. No significant differences in water quality parameters were observed, which suggests that the observed effects were attributable to atrazine exposure. This study revealed that atrazine exposure caused significant growth suppression, altered proximate composition, and histopathological damage in both C. gariepinus and its hybrid progeny, with heightened sensitivity of hybrids to atrazine toxicity. The results highlights the need for cautious management of atrazine use near aquatic ecosystems to mitigate its potential ecological impacts.